2017
DOI: 10.5812/ijp.11273
|View full text |Cite
|
Sign up to set email alerts
|

Lancet Commission on Global Surgery

Abstract: Nearly a third of the global burden of disease require availability of surgical and anesthetic services. However, five billion people currently lack access to safe, affordable surgical and anesthesia care. Each year, appendicitis, hernia, open fracture and other common, treatable surgical diseases result in millions of disabilities and deaths. This is in part due to lack of political will, financial resource allocation, and relevant policy measures. To address these glaring needs, the lancet commission on glob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The increment of non-communicable diseases, trauma and cesarean delivery makes the surgical burden higher than the past. As a result of this, improving patient safety during anesthesia and surgery becomes a major global public health issue [1,2]. The World Health Assembly recognizes this surgical burden in 2015 and accepted strengthening emergency and essential surgical and anesthesia care as a component of universal health coverage for the first time [3].…”
Section: Introductionmentioning
confidence: 99%
“…The increment of non-communicable diseases, trauma and cesarean delivery makes the surgical burden higher than the past. As a result of this, improving patient safety during anesthesia and surgery becomes a major global public health issue [1,2]. The World Health Assembly recognizes this surgical burden in 2015 and accepted strengthening emergency and essential surgical and anesthesia care as a component of universal health coverage for the first time [3].…”
Section: Introductionmentioning
confidence: 99%
“…A little number of publications in surgery may have been caused by two main reasons; inadequate number of surgeons in Rwanda and lack of enough funds to carry out surgical researches. Despite the minimum of 20 surgical doctors per 100,000 population as recommended by the Global Surgery Commission [14], [15], according to the World Bank, in 2016, there was only one surgical specialist per 100,000 population in Rwanda [16]. A study by Shawn J. Rangel et al to measure trends in funding of surgical research showed that compared to nonsurgical ideas, surgical proposals have much lower success rates.…”
Section: Discussionmentioning
confidence: 99%
“…For low-income countries, the situation is quite different. According to the Lancet Commission on Surgery, the cost of surgery and anesthesia causes "catastrophic" health care costs for 33 million people each year [6]. The problem lies mainly in the direct costs of surgical care, which are often high.…”
Section: Surgical Expenditurementioning
confidence: 99%